Acknowledging the past while looking to the future: exploring indigenous child trauma - Swanson, Shanley (Universitetet i Tromsø, 2012)
Trauma affects children from all races, ethnicities, nationalities and socio-economic backgrounds. However, indigenous children may experience trauma differently than their majority population peers due to traumatic histories of colonization and ongoing marginalization. This thesis explores how service providers in Western Montana and Northern Norway conceptualize Native American and Sámi children’s experiences of trauma today. Additionally, I ask if these providers draw links between the historical traumas of the past and current traumatic events facing indigenous children in these two locations. Interviewees spoke about the effects of historical trauma in eight identified themes. The diversity of the themes and concepts discussed imply that providers regard their indigenous clients as being impacted by the historical traumas suffered by indigenous peoples in Montana and Northern Norway. Acknowledging past histories of injustice and focusing future research on the unique resiliencies of indigenous children, families, and communities were two main recommendations for promoting the treatment and understanding of indigenous child trauma. The thesis provides a brief look into the experiences of Native children in Montana and Sámi children in Norway facing trauma, as seen from the eyes of their social workers, therapists and advocates.